Efficacy of first-line treatment options in transplant-ineligible multiple myeloma: A network meta-analysis. (December 2021) - Kiss, Szabolcs; Gede, Noémi; Soós, Alexandra; Hegyi, Péter; Nagy, Bettina; Imrei, Marcell; Czibere, Bernadett; Farkas, Nelli; Hanák, Lilla; Szakács, Zsolt; Eröss, Bálint; Alizadeh, Hussain
Graphical abstract: Highlights: The outcome of transplant-ineligible multiple myeloma improved in the last decades. Choosing the best treatment is difficult due to the ever-growing arsenal of regimens. Continuous update of the standard of care regimens is essential. Our study incorporates 34 regimens and data of 16, 681 patients. Daratumumab containing regimens could be the first preference in first-line treatment. Abstract: Background: Despite major therapeutic advances, the rational choice of the most appropriate first-line regimen in newly diagnosed transplant-ineligible multiple myeloma (TIE-MM) is currently undefined. Aim: We aimed to identify the most effective first-line treatment for TIE-MM patients. Methods: A total of 37 articles, including 34 treatments and 16, 681 patients, were included in this Bayesian network meta-analysis. The outcomes of interest were risk ratios (RR) for progression-free survival (PFS) and overall survival (OS). Results: Based on surface under cumulative ranking curve values, daratumumab-bortezomib-melphalan-prednisone (Dara-VMP) and daratumumab-lenalidomide-dexamethasone (Dara-Rd28) showed superiority compared to other combinations regarding 12-, 24-, 36-, and 48-month PFS. Dara-VMP also ranked first for 12-, 24-, 36-, and 48-month OS. Conclusion: Our finding supports the incorporation of daratumumab into first-line regimens. Additionally, these results highlight the relative benefit of incorporating novel agents like monoclonal antibodies, immunomodulatory derivatives, and proteasome inhibitors in combination with the currently existing treatment options.